High‐throughput sequencing reveals key genes and immune homeostatic pathways activated in myeloid dendritic cells by Porphyromonas gingivalis 381 and its fimbrial mutants. (16th October 2015) - Arjunan, P.; El‐Awady, A.; Dannebaum, R.O.; Kunde‐Ramamoorthy, G.; Cutler, C.W.
Summary: The human microbiome consists of highly diverse microbial communities that colonize our skin and mucosal surfaces, aiding in maintenance of immune homeostasis. The keystone pathogen Porphyromonas gingivalis induces a dysbiosis and disrupts immune homeostasis through as yet unclear mechanisms. The fimbrial adhesins of P. gingivalis facilitate biofilm formation, invasion of and dissemination by blood dendritic cells; hence, fimbriae may be key factors in disruption of immune homeostasis. In this study we employed RNA‐seqencing transcriptome profiling to identify differentially expressed genes (DEGs) in human monocyte‐derived dendritic cells (MoDCs) in response to in vitro infection/exposure by Pg 381 or its isogenic mutant strains that solely express minor‐Mfa1 fimbriae (DPG3), major‐FimA fimbriae (MFI) or are deficient in both fimbriae (MFB) relative to uninfected control. Our results yielded a total of 479 DEGs that were at least two‐fold upregulated and downregulated in MoDCs significantly ( P ≤ 0.05) by all four strains and certain DEGs that were strain‐specific. Interestingly, the gene ontology biological and functional analysis shows that the upregulated genes in DPG3‐induced MoDCs were more significant than other strains and associated with inflammation, immune response, anti‐apoptosis, cell proliferation, and other homeostatic functions. Both transcriptome and quantitative polymerase chain reaction results show that DPG3, which solely expresses Mfa1, increased ZNF366, CD209, LOX1, IDO1, IL‐10, CCL2, SOCS3, STAT3 and FOXO1 gene expression. In conclusion, we have identified key DC‐mediated immune homeostatic pathways that could contribute to dysbiosis in periodontal infection with P. gingivalis .